Co-Movement of Profitability and Bank Concentration in Turkey: a Wavelet Coherence Approach - UMARBEYLI, SUKRU; KIRIKKALELI, DERVIS (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT There has been an increased focus among recent studies on bank profitability. However, there is a gap in the literature in terms of the relationship and causalities between profitability and bank concentrations. To close this gap, this study investigates whether the concentrations of 5 and 7 banks have an impact on bank profitability by using the wavelet coherence technique covering the period 1995Q1-2017Q3. As expected, it is observed that bank profitability and banking concentrations of 5 and 7 banks significantly fluctuated in the period 2000 and 2003. In Turkey, bank concentrations significantly cause the banks’ profitability at different time periods.RESUMEN Ha habido un mayor enfoque entre los estudios recientes sobre la rentabilidad bancaria. Sin embargo, existe una brecha en la literatura en términos de la relación y causalidades entre la rentabilidad y las concentraciones bancarias. Para cerrar esta brecha, este estudio investiga si las concentraciones de 5 y 7 bancos tienen un impacto en la rentabilidad bancaria mediante el uso de la técnica de coherencia wavelet que cubre el período 1995Q1-2017Q3. Como era de esperar, se observa que la rentabilidad bancaria y las concentraciones bancarias de 5 y 7 bancos fluctuaron significativamente en el período 2000 y 2003. En Turquía, las concentraciones bancarias causan significativamente la rentabilidad de los bancos en diferentes períodos.